A new proposal for the use of the focal animal technique in buffaloes in the Eastern Amazon - Silva, Welligton Conceição da; Silva, Jamile Andréa Rodrigues da; Gouveia Júnior, Amauri; de Alvarenga, Adriano Braga Brasileiro; Barbosa, Antônio Vinícius Correa; Silva, Éder Bruno Rebelo da; Pereira dos Santos, Maria Roseane; Lourenço-Júnior, José de Brito; Camargo Júnior, Raimundo Nonato Colares; Silva, André Guimarães Maciel e (Frontiers in Veterinary Science, 2023)
This study aims to present a proposal for using the focal animal recording technique to evaluate the welfare of buffaloes and to verify the association between each behavior and thermal comfort indices. The study was conducted in an experimental paddock located in Santarém, Pará, Brazil. A total of 10 female Murrah animals were used. The behavior of the animals was recorded during the day, with the use of three trained observers, for 72 consecutive h. Climatic variables were collected, and the Temperature–Humidity Index (THI) and the practical Buffalo Comfort Climatic Conditions Index (BCCCIp) were determined. The multivariate technique of principal components and Spearman’s correlation were employed. BCCCIp and THI were outside the thermal comfort zone at different times of the day. Grazing (P) was more frequent in the coldest hours of the day, while rumination occurred at different periods, mainly during the daytime and frequently in a lying position. There was a positive correlation between idle lying behavior and average temperature—Tmed (r = 0.583; p < 0.028), THI (r = 0.432; p < 0.034), and BCCCIp (r = 0.554; p < 0.049). There was a positive correlation between grazing and Tmed (r = 0.665; p < 0.0004) and BCCCIp (r = 0.583; p < 0.036). The standing idle behavior negatively correlated with Tmed (r = −0.718; p < 0.0001), THI (r = −0.522; p < 0.008), and BCCCIp (r = −0.8076; p < 0.0008). The lying ruminating behavior had a positive correlation with Tmed (r = 0.586; p < 0.002), THI (r = 0.477; p < 0.018), and BCCCIp (r = 0.8033; p < 0.0009). Furthermore, ruminating while standing correlated positively with Tmed (r = 0.680; p < 0.0003). The adaptation of the focal animal technique, with six observers evaluating each animal for 6 min through filming, proved to be efficient in pointing out the different behaviors of buffalo raised in Eastern Amazon fields under heat stress at different times of the day.